Epidemiologic Characteristics of Healthcare-Associated Outbreaks and Lessons Learned from Multiple Outbreak Investigations. (4th October 2017) - Kanamori, Hajime; Weber, David J; Gergen, Maria; Dibiase, Lauren; Sickbert-Bennett, Emily; Rutala, William A
Abstract: Background: Single outbreaks due to a specific pathogen(s) and a reservoir have often been reported in healthcare settings, but the frequency of multiple outbreaks at an academic hospital over time and the value of routine molecular typing have not been analyzed. Here, we examined epidemiologic features of healthcare-associated outbreak investigations with a focus on the usefulness of molecular analysis. Methods: Healthcare-associated outbreak investigations at an academic hospital during January 2012–December 2016 were retrospectively reviewed through an institutional healthcare-associated infection (HAI) data based on comprehensive hospital-wide surveillance, monthly reports to the hospital infection control committee, and reports of pulsed-field gel electrophoresis (PFGE) analysis. Results: Fifty-one healthcare-associated outbreaks (annual range 8-15), including 26 (51%) outbreaks in ICUs and 25 (49%) outbreaks in non-ICUs, and 263 infected/colonized patients (median 4, range 1–20) involved in these outbreaks were identified (Figure 1). The frequency of pathogens varied greatly by affected location, specifically multidrug-resistant organisms (MDROs) in ICUs and gastroenteritis in non-ICUs ( Clostridium difficile, norovirus, adenovirus) (Figure 2, 3). Outbreaks in ICUs significantly tended to reoccur more commonly than those in non-ICUs ( P = 0.0001). Notably, all outbreaks were limited to approximately one-third of all units with some repeated cases of same pathogens. Forty-seven (92.2%) outbreaks resulted in HAIs. Of 16 outbreaks due to a bacterial pathogen (total 99 bacteria isolates, median 4.5, range 2–20) evaluated by PFGE, 12 (75%) included some indistinguishable strains, suggesting person-to-person transmission or a common source. PFGE were more frequently performed in ICU outbreaks than in non-ICU outbreaks ( P = 0.0006). A majority of outbreaks were terminated rapidly by enhanced control measures. Seven (13.7%) outbreak investigations led to closure of the affected location. Conclusion: This study demonstrated significant gaps in epidemiologic characteristics of multiple outbreaks between ICUs and non-ICUs as well as the value of molecular typing in understanding the epidemiology of outbreaks. Disclosures: All authors: No reported disclosures.